STUDI DESKRIPTIF KESEHATAN MENTAL REMAJA - Mariska Aryono, Marcella (Widya Warta, 2021)
The main objective of this study was to determine the mental health of early adolescents in Surabaya. This study was a quantitative descriptive research. A total 750 respondents were involved in this study throughout purposive sampling technique who had characteristics aged 11 to 15 years, able to read and write, and lived with their parents. The Mental Health Continuum - Short Form (MHC-SF) were administered to determine the mental health of adolescents. The data were analyzed by descriptive analysis. Based on the result of the data analysis, it could be concluded that 577 early adolescents (76,93%) in Surabaya fit the criteria for flourishing. This means that adolescents are able to achieve well-being but they still need to develop skills which can enhance the social well-being. The rest of the findings revealed that 21,73% fit the criteria of moderate mental healthy category and 1,33%. fit the criteria of languishing category.